The Effectiveness of Podcast-Based Learning for Improving Listening Skills: A Ubiquitous Learning Approach - Yaredi Waruwu; Aung Myint; Nandar Hlaing (International Journal of Language and Ubiquitous Learning, 2025)
Background. The widespread availability of podcasts and the ubiquity of mobile devices enable learners to access diverse listening materials anytime and anywhere, making this approach highly suitable for ubiquitous learning. Purpose. This study aimed to evaluate the effectiveness of podcast-based learning in improving learners’ listening comprehension skills by employing a ubiquitous learning approach. It also sought to examine learners’ engagement and perceptions of the effectiveness of podcast-based learning compared to traditional listening instruction. Method. The research employed a quasi-experimental design involving two groups of learners. The experimental group used podcasts as the primary listening tool, while the control group relied on traditional listening methods. Results. The findings revealed a significant improvement in listening comprehension among learners in the podcast-based learning group compared to those in the control group. In addition, learners exposed to podcast-based learning reported higher levels of engagement, satisfaction, and perceived effectiveness than those using traditional methods. Conclusion. The study concludes that podcast-based learning is an effective and engaging tool for enhancing listening comprehension, particularly in contexts where traditional classroom-based learning is limited or not feasible.